(untitled) (Revista de sociología clínica, 2023)
The teaching and working world has been disrupted by developments known as the 4th Industrial Revolution. As we grappled with the Covid-19 epidemic the world saw massive disruptions in how and where we work, teach, learn and socialize. As moves to continue the social via virtual platforms increased as a result of Covid-19 restrictions we saw disruptions in everyday social meaning making. This article via reflections from personal observation and conversations with colleagues engages with the idea of voice recognition as an important social cue in virtual interactions. The article shows how taken for granted social markers of engagement can be rendered useless in context were the only connector to the people you are interacting with is their voice. The article challenges us to engage with the following questions: What impacts does the move to virtuality have on social engagements that allow us to humanize each other? What can we do to maintain the important social cues important for meaning making in context of teaching, counseling, consultation as we see many of these roles move to the virtual space?